On the Gröbner bases of some symmetric systems and their application to coding theory. - Mora, Teo (Journal of symbolic computation.)
The Gröbner bases of the ideal generated by the symmetric functions are presented. Moreover we show how they can be fruitfully applied to a problem arising from coding theory.